Associations of Pet Ownership with Wheezing and Lung Function in Childhood: Findings from a UK Birth Cohort. - Simon M Collin; Raquel Granell; Carri Westgarth; Jane Murray; Elizabeth S Paul; Jonathan A C Sterne; A John Henderson (PLoS ONE)
Background Asthma is a heterogeneous condition and differential effects of pet ownership on non-atopic versus atopic asthma have been reported. The aim of this study was to investigate whether pet ownership during pregnancy and early childhood was associated with wheezing from birth to age 7 years and with lung function at age 8 years in a UK population-based birth cohort. Methods Data from the Avon Longitudinal Study of Parents and Children (ALSPAC) were used to investigate associations of pet ownership at six time-points from pregnancy to age 7 years with concurrent episodes of wheezing, wheezing trajectories (phenotypes) and lung function at age 8 years using logistic regression models adjusted for child's sex, maternal history of asthma/atopy, maternal smoking during pregnancy, and family adversity. Results 4,706 children had complete data on pet ownership and wheezing. From birth to age 7 years, cat ownership was associated with an overall 6% lower odds of wheezing (OR=0.94 (0.89-0.99)). Rabbit and rodent ownership was associated with 21% (OR=1.21 (1.12-1.31)) and 11% (OR=1.11 (1.02-1.21)) higher odds of wheezing, respectively, with strongest effects evident during infancy. Rabbit and rodent ownership was positively associated with a 'persistent wheeze' phenotype. Pet ownership was not associated with lung function at age 8 years, with the exception of positive associations of rodent and bird ownership with better lung function. Conclusions Cat ownership was associated with reduced risk, and rabbit and rodent ownership with increased risk, of wheezing during childhood. The mechanisms behind these differential effects warrant further investigation.